2008
DOI: 10.1192/pb.bp.107.018424
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatry in the UK: national survey of existing service provision

Abstract: Aims and MethodTo elucidate and describe current neuropsychiatry service provision in the UK. A questionnaire was developed and posted to members of the Royal College of Psychiatrists who had expressed an interest in neuropsychiatry. the responses were tabulated and analysed using descriptive statistics and SPSS version 11.0 for Windows. the neuropsychiatry services provided, sources of referrals, setting of the services and funding streams are described.ResultsOut of 251 respondents, 70 reported providing a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…One third of respondents indicated that fewer than half their patients would be offered ≥1 psychotherapy session. Despite an increasing acknowledgement of the interface between neurology and psychiatry, neuropsychiatry care pathways are relatively under-developed [ 26 ]. Indeed, there is variable involvement of psychiatrists and psychologists in the assessment and management of DS patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One third of respondents indicated that fewer than half their patients would be offered ≥1 psychotherapy session. Despite an increasing acknowledgement of the interface between neurology and psychiatry, neuropsychiatry care pathways are relatively under-developed [ 26 ]. Indeed, there is variable involvement of psychiatrists and psychologists in the assessment and management of DS patients.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, there is variable involvement of psychiatrists and psychologists in the assessment and management of DS patients. This is despite increased recognition that neuropsychiatric disorders, such as DS, may cause distress to patients and their carers, disability, burden and loss of productivity [ 26 ]. More evidence would contribute to national and local discussions about what treatments should be provided for patients with DS patients.…”
Section: Introductionmentioning
confidence: 99%
“…
‘two‐thirds of neuropsychiatry services that had existed for more than a decade, a significant portion had not expanded in recent years and a significant number was forced to reduce in size’(11).
…”
Section: The United Kingdom Scenariomentioning
confidence: 99%
“…Such plateaued progress of these assessed practices was attributed to the main focus of ‘national service framework for mental health on providing comprehensive community services to the public’(11). It highlights the change in focus of mental health services, in favour of providing local services.…”
Section: The United Kingdom Scenariomentioning
confidence: 99%
“…5 At the height of the NHS expansion, a national survey of neuropsychiatry services revealed them to be ‘patchy’ and ‘grossly inadequate’, and discovered that most of the neuropsychiatry services existed from pre-NSF days. 6 Historically, neuropsychiatry services developed at certain national or regional centres, such as a national hospital, significantly before NSF or current commissioning arrangements. They continued to serve or were developed at certain regional centres in an ad hoc way dependent on local clinical enthusiasm or leadership.…”
mentioning
confidence: 99%